Implementasi Program Peningkatan Mutu Profesionalitas Guru di Madrasah Aliyah Negeri 1 Padang Lawas - Wahyudin Nur Nasution; Mohammad Al Farabi; Risni Hayati Nasution (SAP (Susunan Artikel Pendidikan), 2022)
This study aims to analyze the professional quality of teachers, planning teacher quality improvement programs, implementing teacher development programs and the results of implementing work quality improvement programs at Madrasah Aliyah Negeri 1 Padang Lawas Barum. Old Field. This study applied a qualitative method that focuses on the description and analysis of events that occur naturally, events that use the logic of scientific thinking. The approach used in this study was a phenomenological approach. Data collection techniques in this study were (a) interviews; b) observation; (c) documents. The data analysis techniques used in this study were: (a) data minimization; b) data presentation; (c) Results. The results of this study were (1) Teacher Development Program Planning at Madrasah Aliyah Negeri 1 Padang Lawas, which are a) Academic Teacher Development Program for MAN 1 Padang Lawas and b) Teacher Development Program for MAN 1 Padang Lawas. (2) Implementing the Teacher Development Program at Madrasah Aliyah Negeri 1 Padang Lawas through further education through academic qualifications. Academic assessment programs to consider: Qualification objectives, program format, location, and supporting resources.